A holistic approach to chronic pain management that involves all stakeholders: change is needed. (2nd September 2015) - Kress, Hans-Georg; Aldington, Dominic; Alon, Eli; Coaccioli, Stefano; Collett, Beverly; Coluzzi, Flaminia; Huygen, Frank; Jaksch, Wolfgang; Kalso, Eija; Kocot-Kępska, Magdalena; Mangas, Ana Cristina; Ferri, Cesar Margarit; et al.
Abstract: Chronic pain affects a large proportion of the population, imposing significant individual distress and a considerable burden on society, yet treatment is not always instituted and/or adequate. Comprehensive multidisciplinary management based on the biopsychosocial model of pain has been shown to be clinically effective and cost-efficient, but is not widely available. A literature review of stakeholder groups revealed many reasons for this, including: i) many patients believe healthcare professionals lack relevant knowledge, and consultations are rushed, ii) general practitioners consider that pain management has a low priority and is under-resourced, iii) pain specialists cite non-adherence to evidence-based treatment, sub-optimal prescribing, and chronic pain not being regarded as a disease in its own right, iv) nurses', pharmacists' and physiotherapists' skills are not fully utilized, and v) psychological therapy is employed infrequently and often too late. Many of the issues relating to physicians could be addressed by improving medical training, both at undergraduate and postgraduate levels – for example, by making pain medicine a compulsory core subject of the undergraduate medical curriculum. This would improve physician/patient communication, increase the use of standardized pain assessment tools, and allow more patients to participate in treatment decisions. Patient care would also benefit from improved training for other multidisciplinary team members; for example, nurses could provide counseling and follow-up support, psychologists offer coping skills training, and physiotherapists have a greater role in rehabilitation. Equally important measures include the widespread adoption of a patient-centered approach, chronic pain being recognized as a disease in its own right, and the development of universal guidelines for managing chronic non-cancer pain. Perhaps the greatest barrier to improvement is lack of political will at both national and international level. Some powerful initiatives and collaborations are currently lobbying policy-making bodies to raise standards and reduce unnecessary pain – it is vital they continue.